The application of dual energy X-ray soil screening in forensic archaeology. Issue 5 (September 2022) - Kent, Daniel; Márquez-Grant, Nicholas; Lane, David
Highlights: Forensic casework often requires sieving through soil to search for human remains and other items. The only soil search methods more commonly available are wet and dry sieving. This study explored the use of X-ray baggage scanners to search for items in soil. The baggage scanner provided a quick and easy way to detect items within soil. Abstract: The need to forensically search soil for small artefacts at a burial site or traces of evidence in a deposition site is a common task shared by investigators and forensic archaeologists. In forensic casework, the importance of finding small pieces of evidence, such as personal effects or ballistic fragments, cannot be overstated as it can assist in the positive identification of the deceased, give an insight into the manner and cause of death, and identify any perpetrators. The soil search methods known as wet and dry sieving, are cumbersome, time-consuming and have limited success for some soil types. This often leads to the decision not to search, resulting in missed opportunities to identify potential evidence. The primary aim of this study was to investigate if a dual energy X-ray baggage scanner could be used to search for items of potential forensic interest in soil. A trial was conducted using a Smiths Detection ScanTrailer 100100 V-2is mobile X-ray inspection system to establish if it could be used to detect organic, inorganic, and metallic items located within soil. The soil type and natural variables such as water and organic content were adjusted to simulate different environments. The baggage scanner was found to provide a quick and easy way to detect items contained within various soil types, particularly in a sand rich matrix. It is estimated that using this method to search 1 m 3 of soil, when broken down into samples that are < 13 cm in depth, would take around one hour to complete, compared with 100 to 150 person-hours by manual sieving. This is believed to be the first use of dual energy X-ray technology for this purpose and shows the potential for further research and use of this method in forensic archaeology.